2018
DOI: 10.3892/mmr.2018.9010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory roles of miR‑9 on papillary thyroid cancer through targeting BRAF

Abstract: MicroRNA‑9 (miR‑9) is reported to be underexpressed in papillary thyroid carcinoma (PTC) tissues; however, the molecular mechanisms underlying the implication of miR‑9 in PTC have yet to be elucidated. The present study aimed to explore the potential roles of miR‑9 in PTC. PTC tissue samples and paired non‑cancerous adjacent tissues were collected from 60 patients with PTC. The human TPC‑1 thyroid gland papillary carcinoma cell line was used to investigate the molecular mechanisms underlying the roles of miR‑9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Moreover, miR-196b promotes cell migration and invasion by targeting FOXP2 in hepatocellular carcinoma and regulates self-renewal, differentiation, and transformation by targeting HOXC8 in breast cancer stem cells [37,38]. miR-9 has an inhibitory role in papillary thyroid cancer by targeting BRAF and reduces metastatic behavior in triple-negative breast cancer by targeting NOTCH1 [39,40]. However, the roles of these miRNAs in lung cancer and their potential therapeutic applications have not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-196b promotes cell migration and invasion by targeting FOXP2 in hepatocellular carcinoma and regulates self-renewal, differentiation, and transformation by targeting HOXC8 in breast cancer stem cells [37,38]. miR-9 has an inhibitory role in papillary thyroid cancer by targeting BRAF and reduces metastatic behavior in triple-negative breast cancer by targeting NOTCH1 [39,40]. However, the roles of these miRNAs in lung cancer and their potential therapeutic applications have not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our finding, Sondermann A et al [29] observed the significantly downregulated expression of miR-9 in patients with recurrent Table 3 Relationships between clinicopathological characteristics of PTC patients and BRAF V600E mutation status and BANCR and miR-9 expression in carcinoma tissue (n = 51) PTC, which can be used as a prognostic indicator of PTC. Gu Y et al [30] found that miR-9 may inhibit the activity of PTC cells and tumor growth by directly targeting the expression of BRAF in PTC. In the present study, patients with BRAF V600E mutation have a higher rate of BANCR overexpression and tended to have a lower rate of miR-9 overexpression (P = 0.057), and there is a negative association were found between BANCR and miR-9 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the GC contents of all primers were between 50-60 percent, melting temperature was almost 62 °C and there were no more than four repeats of bases. Primers were not self-complementary, thus the chance of primer dimerization during reaction were zero ( Yasumura et al, 2004 , Charette et al, 2010 , Xu et al, 2010 Yang et al, 2015 , Singh et al, 2017 , Xu et al, 2017a , Xu et al, 2017b , Gu et al, 2018 , Liu et al, 2018 , Kalimutho et al, 2019 ). Table 1 .…”
Section: Methodsmentioning
confidence: 99%